Os saberes etnofarmacobotânicos na Comunidade Sucuri, Cuiabá - Mato Grosso - Gonçalves, Karina Gondolo (2016)
The Ethnobotany is an interdisciplinary field that includes the study and interpretation of knowledge, cultural significance, management and traditional uses of flora elements. Already Ethnopharmacobotany seeks to allow the use of medicinal plants which have pharmacological activities that are involved in different situations of life of man and his social group. The objective of this research investigating and analyzing the empirical knowledge of the Sucuri community in Cuiaba - MT on the use of local flora with a focus on medicinal plants, highlighting their use of purposes, forms of uses and therapeutic indications and how to perform Ethnopharmacobotany survey of species of the most significant medical ethnocategory for this community and have reached 50% or more in the calculation of the relative importance of the main uses of agreement (Pcup). The methodological aspect to the ethnobotanical data abordaou qualitative and quantitative treatments. The qualitative used the snowball technique with application of the pretest, semi-structured and open interviews, guided tour and photographic record. Quantitatively it was used Informant Consensus, which evaluated the loyalty level (NF) Correction Factor (FC) and the relative importance of use agreement (Pcup) between informants users of medicinal plants. They interviewed 44 residents of 36 households visited, mostly female. The age ranged from 25 to 84 years. As for the origin 85% are in the state of Mato Grosso and the rest of the Paraíba state, Parana and Mato Grosso do Sul. In respect to time residing in the community almost half of the interviewees are more than 30 years and the time among all respondents ranged from two months to 76 years of stay in Sucuri. The level of education ranged from illiterate to higher level with emphasis on complete elementary school with approximately 30% and finished high school with 25%. In total they were cited 214 plant species belonging to 74 botanical families, with 1134 citations, and 120 of these species were cited by interviewees for medical ethnocategory that are distributed in 48 botanical families, with 426 citations. The most significant medicinal species were: Plectranthus barbatus Andrews (boldo) cited by 18 interviewees representing an Pcup 89%, Hymenaea courbaril L. (Jatobá) with 17 citations and 61% of Pcup then Strychnos pseudoquina A. St.-Hil . (quina) with 14 citations and Pcup 66%, following Matricaria recutita L. (camomila), 14 quotes and 55% (Pcup), and finally Phyllanthus niruri L. (quebra-pedra), 10 quotes and 55% (Pcup). The empirical use of boldo appointed by the informants to treat diseases of the digestive system may be related to the occurrence of caryophyllene as a major component of its essential oil present in the glandular and non-glandular trichomes. The jatobá which was empirically indicated for diseases of the respiratory system is linked to the anti-inflammatory and antioxidant xv 16 properties contained in this plant. The alkaloids present in the bark of the quina has antimicrobial activity justifying its popular use as a dewormer. Camomila is used by the interviewees, mainly as soothing, this chemically supported by the existence of bioactive as chamazulene and alpha- bisabolol. Studies also have demonstrated the diuretic, analgesic and kidney stones reducer aqueous extract made from the leaves, aerial parts or whole quebra-pedra break. It can be said that the study population knows the local plant diversity, the management, the origin, the parties used the forms of use and the diseases treated with the use of medicinal plants. It could also record the current situation and warn of the importance of rational use of flora surrounding the process of environmental sustainability related to plant communities as a permanent source of use.